Understanding Social Loafing Among Senior High School Learners: Proposed Evidence-Based Teaching-Learning Intervention Strategies (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This mixed-methods explanatory sequential study investigated the phenomenon of social loafing among Grade 12 learners at Leyte National High School in the Philippines. Recognizing that collaborative learning is a cornerstone of the Philippine Department of Education curriculum, this study addressed a critical gap in local literature by exploring the extent, causes, consequences, and solutions to social loafing within this specific institutional context. Quantitative data were collected through surveys, followed by qualitative data gathered via in depth interviews to provide deeper explanation of the initial findings.The findings reveal a notable self-other discrepancy, where learners rarely identify themselves as loafers but readily recognize loafing behavior in their peers. Key causes of social loafing include the absence of individual grading, the perception that personal input is unnecessary for group success, large group sizes, and unclear individual accountability. Qualitative analysis uncovered additional personal factors such as laziness, lack of interest, lack of competence, fear of judgment, and low academic ambition. Group dynamic factors include poor communication and permissive leadership, while external factors encompass home responsibilities and technological constraints.Consequences of social loafing extend beyond poor academic performance to include delayed submissions, overburdened active members experiencing stress and burnout, resentment and conflict among team members, decreased motivation, and damaged group cohesion. Proposed solutions include establishing clear and equal roles, implementing individual grading and peer evaluations, applying meaningful consequences for non-contribution, fostering open communication, setting strict deadlines with monitoring, and reducing group size. The study concludes that addressing social loafing requires structural, and relational interventions to create equitable and productive collaborative learning environments.